Meningkatkan Upaya Pelestarian Lingkungan Melalui Kegiatan Penghijauan Dengan Memanfaatkan Lahan Kosong - Feby Yolanda Feby; Maya Yuliana; Azura Luthfiyah; Rahmat Hidayat Hidayat; Neng Sholihat (LPPM UMRI, 2022)
Conceptually, what is able to overcome problems regarding the environmental crisis is to carry out environmental conservation activities in the form of reforestation. The word preservation comes from the word